Penyuluhan Kesadaran Warga tentang Pentingnya Penggunaan Air Bersih Untuk Kebutuhan Mandi, Cuci, Kakus (MCK) di Desa Margaluyu - Noerma Kurnia Fajarwati; Lilis Lilis; Eunike Priskilla; Kamilia Salsabila; Herlina Herlina; Sumiyati Wirdaningsih; Dede Milawati; Rizki Arif Perdana (Jurnal Informasi Pengabdian Masyarakat, 2024)
Raising awareness among residents about the importance of using clean water for bathing, washing and toileting (MCK) needs in Margaluyu Village is a community service effort aimed at improving the health and welfare of the community. Margaluyu Village, which has abundant natural resource potential, still faces serious challenges related to access and use of clean water. Through this activity, outreach and education are carried out regarding the impact of using polluted water on health, as well as the importance of good sanitation practices. The methods used include interactive counseling, group discussions and practical demonstrations. The results of the activity show an increase in residents' knowledge about the importance of clean water and healthy toilet practices. It is hoped that with this outreach, the community will be able to adopt better habits in using clean water, as well as contribute to improving the quality of life and environment in Margaluyu Village. It is also hoped that this activity can become a model for similar initiatives in other regions tha